1989
DOI: 10.1007/bf00037889
|View full text |Cite
|
Sign up to set email alerts
|

Cytological mechanism of 2n pollen formation and unilateral sexual polyploidization in Lolium

Abstract: Plants of Lolium perenne, L . multiflorum and L. hybridum (331, 51 and 18, respectively) were screened for 2n pollen production . The screening was based on the size differences that are expected to be found between n and 2n pollen of a plant . It was found that 28 plants of perennial ryegrass -belonging to 13 cultivarsproduced pollen grains of heterogenous size (big and small) . The estimated frequency of big pollen grain production was higher than 10% in ten out of 28 plants and in three of them it reached a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 12 publications
(12 reference statements)
3
20
0
Order By: Relevance
“…Application of functional 2n gametes has become an important tool for the production of polyploid cultivars in different plant species like potato (Mendiburu and Peloquin 1977;Den Nijs and Peloquin 1977), wheat (Jauhar 2003), Lolium (Sala et al 1989), Aspagarus (Camadro 1994), Medicago sativa (Barcaccia et al 1998) and Lilium (Lim et al 2001;Barba-Gonzalez et al 2005;Zhou et al 2008). The traditional method to breed the triploid lilies is to obtain the tetraploid as a first step by mitotic polyploidization.…”
Section: Discussionmentioning
confidence: 99%
“…Application of functional 2n gametes has become an important tool for the production of polyploid cultivars in different plant species like potato (Mendiburu and Peloquin 1977;Den Nijs and Peloquin 1977), wheat (Jauhar 2003), Lolium (Sala et al 1989), Aspagarus (Camadro 1994), Medicago sativa (Barcaccia et al 1998) and Lilium (Lim et al 2001;Barba-Gonzalez et al 2005;Zhou et al 2008). The traditional method to breed the triploid lilies is to obtain the tetraploid as a first step by mitotic polyploidization.…”
Section: Discussionmentioning
confidence: 99%
“…In Solanum plants, 2n pollen production ranged from 2 to 10% whilst 2n egg production ranged from 4-9 to 23% Werner & Peloquin, 1991a). In Dactv/is glotnerata, the frequency of 2n pollen has been found to vary between 0-1 and 14% in different individual plants and 2n egg frequency from 0-1 to 26% , Furthermore, the frequency of 2n gamete production 0-1-4-9 0-14-14 --28 < 1-35-6 (5-5) 1-3-34 0-3-1-9 < 1-28-6 0-11-26 (5-5) 4-9-23 0-014-0-5 0-4-2 Ray & Tokach, 1992Maceira et al, 1992Sala et al, 1989Negri, 1992Hahn et al, 1990Veronesi et al, 1986Bullita & Smith, 1992Shoemaker-Megalos & Ballington, 1988Ortiz et al, 1992De Haan et al, 1992Veronesi et al, 1986Werner & Peloquin, 1991aShoemaker-Megalos & Balhngton, 1988 Masuelli et al, 1992Parrott et al, 1984 has also been found to be highly variable within the flowers of an individual plant (Veilleux & Lauer, 1981;McCoy, 1982;Veilleux, McHale & Lauer, 1982;Veilleux, 1985). For instance, McCoy (1982) reported that 2n pollen production varied from 4 to 37% among flowers of a single plant of Medicago sativa and Veilleux et al (1982) discovered that 2n pollen production ranged from 5-6 to 61-7% among anthers from a single bud in Solanum.…”
Section: Kruquuncy O1--2n Gametij Productionmentioning
confidence: 99%
“…Wagenvoort et al, 1990Lelley et al, 1987Ramanna, 1983Iwanaga, 1984;Werner & Peloquin, 1987;Jongedijk & Ramanna, 1988;Watanabe & Peloquin, 1993Parrott & Smith, 1984Rabe & Haufler, 1992Vorsa, 1986in Ortiz et al, 1992Nassar, 1992Simpson & Davis, 1983 Werner & Peloquin, 1991a Mok & Peloquin, 1975 Stelly & Peloquin, 1986;Watanabe & Peloquin, 1989;Werner & Peloquin, 1987;Zhang et al, 1988Vorsa, 1986in Ortiz et al, 1992Werner & Peloquin, 1987Sala et al, 1989Zhang et al, 1988Nassar, 1992Ray & Tokach, 1992Mok & Peloquin, 1975Ramanna, 1978;Camadro & Peloquin, 1980;Iwanaga & Peloquin, 1982;Watanabe & Peloquin, 1989;Masuelli et al, 1992 Jones, 1990Orjeda et al, 1990Zhang et al, 1988Vorsa & Bingham, 1979Bingham & McCoy, 1979;Tavoletti et al, 1991aMyers et al, 1984Parrott & Smith, 1984Werner & Peloquin, 1991aRay & Tokach, 1992Werner & Peloquin, 1987Wagenvoort et al, 1990…”
Section: Cytological Aspects Of 2n Gamete Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…The frequency of 2n pollen in Actinidia , for example, ranged from 0.7 to 10.3 (Yan et al, 1997) and was lower in Avena vaviloviana, reaching 1.0% (Katsiotis & Forsberg, 1995). Although the production of 2n gametes is under genetic control (Sala et al, 1989, Katsiotis & Forsberg, 1995Calderini & Mariani, 1997) it can also be affected by environmental conditions. Stein (1970) listed several species in which the frequency of 2n gametes varied with the cultivation conditions.…”
Section: Resultsmentioning
confidence: 99%